Zmierzch komedii staroattyckiej? Wybrane problemy Plutosa Arystofanesa - Kostek, Szymon (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2011)
The article is an attempt of interpretation of the main problems of the last saved comedy written by Aristophanes. Personifications of wealth and poverty are a basic object of analysis. We can say that there is wealth and its influence on life of citizens of Athens in the centre of Wealth’s problems. The author of the article gives some opening remarks about Wealth in the context of Attic Old Comedy which is understood as theatrical/dramatic genre. The statements of the commentators of Aristophanes as Angus M. Bowie, Kenneth J. Dover, Anna M. Komornicka, Douglas M. MacDowell, Erich Segal, Martin Revermann or Tadeusz Zieliński are used in the article in order to achieve a result of power of interpretation.
Twilight of the Attic Old Comedy Era. Notes on Aristophanes’ Wealth
Wealth is the last saved Aristophanes’ comedy. This is the presentation of problems of social inequalities but personifications of poverty and wealth are also very important. The researcher’s attention is focused on Wealth which is portrayed as the comedy of borderland. It is difficult to categorize it as an example of Attic Old Comedy. And it is possible to think that the Aristophanes’ work belongs to Greek Middle Comedy. Images of old-Greek gods: Wealth, Zeus, Hermes have fundamental weight here. Also we can notice that Wealth is similar to fairy tale. It presents the vision of utopia which makes possible escape from concerns about daily life.
Keywords: Aristophanes; Wealth; Greek comedy; Attic Old Comedy; Personifications in classic literature; Utopia